PD-L1/PD-1 Pattern of Expression Within the Bone Marrow Immune Microenvironment in Smoldering Myeloma and Active Multiple Myeloma Patients - Costa, Federica; Vescovini, Rosanna; Marchica, Valentina; Storti, Paola; Notarfranchi, Laura; Dalla Palma, Benedetta; Toscani, Denise; Burroughs-Garcia, Jessica; Catarozzo, Maria Teresa; Sammarelli, Gabriella; Giuliani, Nicola (Frontiers in Immunology, 2021)
Background: The PD-1/PD-L1 axis has recently emerged as an immune checkpoint that controls antitumor immune responses also in hematological malignancies. However, the use of anti-PD-L1/PD-1 antibodies in multiple myeloma (MM) patients still remains debated, at least in part because of discordant literature data on PD-L1/PD-1 expression by MM cells and bone marrow (BM) microenvironment cells. The unmet need to identify patients which could benefit from this therapeutic approach prompt us to evaluate the BM expression profile of PD-L1/PD-1 axis across the different stages of the monoclonal gammopathies. Methods: The PD-L1/PD-1 axis was evaluated by flow cytometry in the BM samples of a total cohort of 141 patients with monoclonal gammopathies including 24 patients with Monoclonal Gammopathy of Undetermined Significance (MGUS), 38 patients with smoldering MM (SMM) and 78 patients with active MM, including either newly diagnosed or relapsed-refractory patients. Then, data were correlated with the main immunological and clinical features of the patients. Results: First, we did not find any significant difference between MM and SMM patients in terms of PD-L1/PD-1 expression, on both BM myeloid (CD14+) and lymphoid subsets. On the other hand, PD-L1 expression by CD138+ MM cells was higher in both SMM and MM as compared to MGUS patients. Second, the analysis on the total cohort of MM and SMM patients revealed that PD-L1 is expressed at higher level in CD14+CD16+ non-classical monocytes compared with classical CD14+CD16- cells, independently from the stage of disease. Moreover, PD-L1 expression on CD14+ cells was inversely correlated with BM serum levels of the anti-tumoral cytokine, IL-27. Interestingly, relapsed MM patients, showed an inverted CD4+/CD8+ ratio along with high levels of pro-tumoral IL-6 and a positive correlation between %CD14+PD-L1+ and %CD8+PD-1+ cells as compared to both SMM and newly diagnosed MM patients suggesting a highly compromised immune-microenvironment with low amount of CD4+ effector cells. Conclusions: Our data indicate that SMM and active MM patients share a similar PD-L1/PD-1 BM immune profile, suggesting that SMM patients could be an interesting target for PD-L1/PD-1 inhibition therapy, in light of their less compromised and more responsive immune-microenvironment.